1977
DOI: 10.1111/j.1460-2466.1977.tb01805.x
|View full text |Cite
|
Sign up to set email alerts
|

The Content of Children's Toy and Food Commercials

Abstract: Pre-Christmas Saturday morning message strategies and presentational techniques on national network television programs.Each Saturday morning children might be exposed to as many as fifty toy and food commercials that are carefully designed to teach and persuade them. In addition, the messages present extensive incidental information concerning social attitudes and behavior.A recent set of articles in thisJournal (2,3,4) and the present symposium explore several aspects of this process. However, there have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 2 publications
1
16
0
1
Order By: Relevance
“…Stern and Harmon (1984) reported that 9.3% of ads in programs with signifi cant child viewership had dual-modality disclaimers. In earlier studies, the use of disclaimers varied from 10% with a visual or dual-modality disclaimer (Barcus 1975), to 15% of ads airing after school and 19% of weekend ads having a disclaimer (Barcus 1977), up to 31% with a visual or dualmodality disclaimer (Atkin and Heald 1977). Hoy and Stankey (1993) reported none and Hoy and Andrews (2004) reported 8.5% of the disclosures in their prime-time samples were dual modality.…”
Section: Disclaimers or Disclosuresmentioning
confidence: 96%
“…Stern and Harmon (1984) reported that 9.3% of ads in programs with signifi cant child viewership had dual-modality disclaimers. In earlier studies, the use of disclaimers varied from 10% with a visual or dual-modality disclaimer (Barcus 1975), to 15% of ads airing after school and 19% of weekend ads having a disclaimer (Barcus 1977), up to 31% with a visual or dualmodality disclaimer (Atkin and Heald 1977). Hoy and Stankey (1993) reported none and Hoy and Andrews (2004) reported 8.5% of the disclosures in their prime-time samples were dual modality.…”
Section: Disclaimers or Disclosuresmentioning
confidence: 96%
“…In the non-Christmas portion of the ad year, candy and cereal account for more than 60% of the ads viewed. Toy ads gain center stage in the Christmas season, accounting for 50% or more of all ads aired in that time frame (Atkin & Heald, 1977;Barcus, 1976Barcus, , 1980Condry et al, 1988;Harrison & Marske, 2005;Kunkel, 2001;Kunkel & Gantz, 1992). Content-nutrition coding of current food ads reveals diets exceeding recommended daily values (RDVs) by nearly a cup of sugar.…”
Section: Food and Beverage Products Advertisedmentioning
confidence: 99%
“…Data for 1971and 1975 were derived from the food advertisement logs reported by others (Barcus, 1971;Barcus & Wolkin, 1977). Although several other studies have examined food advertisements on Saturday morning children's television (Atkin & Heald, 1977;Brown, 1977;Cotugna, 1988;Cuozzo, 1971;Doolittle & Pepper, 1975;Gussow, 1972;Kotz & Story, 1994;Winick, Williamson, Chuzmir, & Winick, 1973), they did not report food advertisement logs, were not limited to Saturday morning network programming, and/or presented data more limited in scope for the same time period reported by Barcus (1971) or Barcus and Wolkin (1977).…”
Section: Advertisements For Productsmentioning
confidence: 99%